(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2018)
At present, there is an insufficient level of accounting and analytical support for the activity of hotel enterprises, which makes it impossible to obtain the economic benefit to the full, since it forces executives to save financial and material resources, to calculate the effectiveness of new projects and commercial transactions. There is no single approach to the organization of the accounting and analytical process of hotel enterprises, as it is a specific type of activity consisting of trade, production and provision of services.The article focuses attention on the problems of formation of accounting and analytical support of activity of hotel enterprises and the use of information and analytical base in managing economic activity of economic entities of this industry. International experience shows that the necessary prerequisite for the active and successful promotion of this industry on the domestic market is the integration processes in the European space, which requires the development of modern infrastructure. Accounting and analytical provision of hospitality services is one of the most important management mechanisms that enable to objectively assess the level of economic activity of hotel enterprises. The main perspectives of the development of hotel enterprises are considered, the main aspects that need to be investigated for the purpose of building the accounting and economic support and the introduction of an effective mechanism for managing the financial and economic activities of the hotel business are revealed. In the process of studying accounting and analytical support of activity of hotel enterprises, a number of tasks were identified that covered this mechanism. The necessity of gradual introduction into the accounting and analytical activities of the enterprise elements of management accounting, taking into account international standards and progressive experience regarding modern approaches to the formation of financial results, is substantiated. The stages of formation of accounting and analytical support of hotel activity are emphasized and attention is focused on the problems of their implementation, the solution of which will depend on the effectiveness of the accounting and analytical system of the hotel company, which in general will affect its financial results.